A10.06 Detecting adalimumab serum level and anti-drug antibodies – future tool in monitoring spondyloarthritis patients?. (24th February 2016) - Deaconu, C; Opriş, D; Mazilu, D; Borangiu, A; Groșeanu, L; Negru, M; Constantinescu, C; Săulescu, I; Bojincă, V; Vlad, V; Bălănescu, A; Predețeanu, D; et al.
Abstract : Background and objectives: Anti-TNF agents have highly proved their efficacy in spondylarthritis (SpA) patients, with a good rate of response of approximately 70%. However a third of patients lose response to treatment. Measuring the drug serum level and anti-drug antibodies might lead to identifying the cause of non-response, followed by adjusting the therapeutic scheme. The aim was to determine the utility of determining drug serum adalimumab (ADL) and anti-ADL antibodies in assessing disease activity in SpA patients. Methods: Over a period of 11 months we included 54 SpA patients on ADL, with further exclusion of those who had delayed drug administration or suffered a concomitant infection. Demographic, clinical (disease activity scores) and laboratory (ESR, CRP) data were collected. We measured the determination of interest using Promonitor kits, using the ELISA technique and the statistical analysis was performed with SPSS 20.0. Results: Out of the total 35 patients, 74% were males, the mean age was 40 years old with a mean disease duration of 102 months. HLA B27 was positive in 91% of patients and 28% required sacroiliac joint MRI at diagnosis, being a non-radiographic form. 28% of patients tested positive for Quantiferon and underwent chemoprophylaxis. 22% had history of uveitis before diagnosis and 9% had recurrences while on ADL. 82% of patients had detectable ADL levels. The BASDAI score was significantly higher in patients with undetectable ADL (P < 0.001), with a mean value of 6.3 indicating an inadequate disease control. Furthermore, both ASDAS-ESR and ASDAS-CRP were higher in these patients (P < 0.001). 25% had positive anti-ADL antibodies. Patients with no identified antibodies had lower disease activity scores (BASDAI, ASDAS-VSH and ASDAS-CRP, P < 0.001). Acute phase reactants (ESR, CRP) had a higher value in patients with positive anti-ADL antibodies (P = 0.015 and P < 0.001, respectively). Serum level ADL negatively correlated to the presence of anti-ADL antibodies (r = -0.360, P = 0.034) and to disease activity scores. Conclusions: Undetectable serum drug level together with the presence of anti-drug antibodies and the increase of SpA activity scores indicate the impact of immunogenicity throughout secondary non-responder patients. Prompt identification of these patients might lead to a better adapted therapeutic scheme.